ANALISIS BAUARAN PEMASARAN JASA PADA TINGKAT LOYALITAS KONSUMEN PRIMA FRESHMART DI PROVINSI BALI - NGURAH MADE NOVIANHA PYNATIH (Universitas Mahasaraswati K. Mataram, 2023)
The aims of this study were (1) to determine the direct and indirect effect of implementing Prima Freshmart's marketing mix partially and simultaneously on consumer loyalty in the Province of Bali, (2) to determine the level of consumer loyalty of Prima Freshmart in the Province of Bali. This study used a sample of 115 consumers spread across 33 stores in the Province of Bali. The data analysis technique used in this study used Path Analysis.The results showed that the seven sub-variables and marketing mix variables for Prima Freshmart services in Bali Province had a positive and significant effect on consumer loyalty. The greatest value of the effect on consumer loyalty is the physical means of service, which is equal to 16.33%, while the smallest value of the influence of the service marketing mix is the HR sub variable of 8.37%. For the level of consumer loyalty, it is at the Advocates level (46.06%) and Clients (42.22%). For the Repeat Customers level, the number of consumers is 8.64% and the number of consumers for the First Time Customers level is 2.75%.